Solve the following system of equations by substitution. 𝑦 = 5𝑥 8𝑥 − 3𝑦 = 35 H. (-6, -30) I. (-5, -25) J. (-4, -20

1 answer

To solve this system of equations by substitution, we first need to solve for one variable in one of the equations and then substitute that expression into the other equation.

Given equations:
1) y = 5x
2) 8x - 3y = 35

From equation 1, we can express y in terms of x:
y = 5x

Now substitute y = 5x into equation 2:
8x - 3(5x) = 35
8x - 15x = 35
-7x = 35
x = -5

Now that we have found the value of x, we can substitute it back into y = 5x to find y:
y = 5(-5)
y = -25

Therefore, the solution to the system of equations is (-5, -25). So the correct answer is I. (-5, -25).